Bolivia : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Despite good economic reforms, macroeconomic stability, and a major expansion of the hydrocarbon sector, Bolivia still achieved only modest gains in poverty reduction. Executive Directors stressed the importance of fiscal prudence, domestic taxation, and strengthening of public expenditure management to ensure fiscal sustainability. They commended the central bank for its monetary policy stance. They highlight the need to attain greater equity, transparency, and accountability underpinned by cautious macroeconomic policies. They underscored that Bolivia may face a competitive external environment for its nontraditional exports in the period ahead.